Ha'i Bou - Nur Laila Ibrahim; Nurul Ilmi Idrus (Universitas Muslim Maros, 2019)
Filariasis, which is locally termed as ha’i bou, is one of the potential infectious disease found in the tropical areas. The existing literatures disputes the problem of elephantiasis from a medical perspective, while rarely (if any) the debate about how filariasis is perceived locally (emic perspective) and this is related to how they seek, care for, prevent and treat it. This article fills this gap. This ethnographic study was conducted in Maukaro Subdistrict, Ende, NTT since the area is filariasis endemic with 60% of cases of filariasis sufferers found in some villages. There sixteen informants who participated in this study, consisting of eleven filariasis sufferers, the rest were Puskesmas and Dinas Kesehatan staf, a community leader, and a family member of filariasis sufferer. Data was collected using in-depth interview to explore the local knowledge of the community about filariasis, its etiology, the symptoms and characteristics of filariasis, and how they respond; while observations were made to see how the daily lives of the Maukaro people, especially those who suffer from filariasis, their interactions and the conditions of their surrounding environment. The study indicates that filariasis is socially understood as a curse from God and ancestors (embu mamo nitu pa'i) for intentionally killing animals during the process of searching for food in the forest or in the fields. Filariasis is locally divided into two characteristics, namely ha'i bou fai (female elephantiasis disease) and ha'i bou aki (male elephantiasis disease). Despite the fact that the characteristics of the disease differ by gender, this difference is more associated with whether or not the disease is chronic rather than differences based on gender, and how they deal with it is also genderless. Ha’i bou can be experienced by anyone regardless of gender. While ha’i bou aki is relatively curable as long as it is adequately treated with good self care, ha'i bou fai has so far non curable yet. However, ha'i bou aki can be increased to ha’i bou fai depending on how the patient maintains and takes care of his/her personal hygiene. The Maukaro people believe that the cause of the disease consists of two, namely rangka atas (relating to God / Du'a ngga'e and air / angi) and rangka bawah (related to land, water and environmental conditions). In relation to ha’i bou, the latter is more dominant than the former, and it is believed that the land, water, and environment each have positive and negative characteristics. Not maintaining the environment is likened to